Ganzheitliches Qualitätsmanagement in agilen Groß- Projekten - Fazal-Baqaie, Masud; Güldali, Baris; Grieger, Marvin (Proceedings of Projektmanagement und Vorgehensmodelle 2016)

Concept-Based Engineering of Situation-Specific Migration Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Engels, Gregor; Klenke, Markus (Proceedings of the 15th International Conference on Software Reuse (ICSR))

Multi-device UI Development for Task-Continuous Cross-Channel Web Applications - Yigitbas, Enes; Kern, Thomas; Urban, Patrick; Sauer, Stefan (Current Trends in Web Engineering - ICWE 2016 International Workshops, DUI, TELERISE, SoWeMine, and Liquid Web, Lugano, Switzerland, June 6-9, 2016, Revised Selected Papers)

Engineering Context-Adaptive UIs for Task-Continuous Cross-Channel Applications - Yigitbas, Enes; Sauer, Stefan (Human-Centered and Error-Resilient Systems Development - IFIP WG 13.2/13.5 Joint Working Conference 6th International Conference on Human-Centered Software Engineering, HCSE 2016, and 8th International Conference on Human Error, Safety, and System Development, HESSD 2016 Stockholm, Sweden, August 29-31, 2016, Proceedings)

Customized UI Development Through Context-Sensitive GUI Patterns - Yigitbas, Enes; Sauer, Stefan (Mensch und Computer 2016 - Workshopband, Aachen, Germany, September 4-7, 2016)

Towards a Task Driven Approach Enabling Continuous User Requirements Engineering - Fischer, Holger Gerhard; Rose, Mirko; Yigitbas, Enes; Forbrig, Peter (Joint Proceedings of REFSQ-2016 Workshops, Doctoral Symposium, Research Method Track, and Poster Track co-located with the 22nd International Conference on Requirements Engineering: Foundation for Software Quality {(REFSQ} 2016), Gothenburg, Sweden, March 14, 2016.)

Towards a Model-Driven Method for Reusing Test Cases in Software Migration Projects - Jovanovikj, Ivan; Grieger, Marvin; Yigitbas, Enes (Softwaretechnik-Trends, Proceedings of the 18th Workshop Software-Reengineering & Evolution (WSRE) & 7th Workshop Design for Future (DFF))

The Impact of Communication Patterns on Distributed Self-Adjusting Binary Search Tree - Strothmann, Thim Frederik (Journal of Graph Algorithms and Applications)
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm that is closely related to the over thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided. To do so, the process of self-adjustment is modeled similarly to a basic network creation game in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and that convergence is related to certain structures of the communication interests, which we call conflicts. We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well. Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

FPGA-based acceleration of high density myoelectric signal processing - Boschmann, Alexander; Agne, Andreas; Witschen, Linus; Thombansen, Georg; Kraus, Florian; Platzner, Marco (2015 International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing)
Integrating apps on mobile devices into applications running on other devices is usually difficult. For instance, using a messenger on a smartphone to share a text written on a desktop computer often ends up in a cumbersome solution to transfer the text, because many applications are not designed for such scenarios. In this paper, we present an approach enabling the integration of apps running on Android devices into applications running on other devices and even other platforms. This is achieved by specifying adapters for Android apps, which map their services to a platform-independent service interface. For this purpose, we have developed a domain-specific language to ease the specification of such mappings. Our approach is applicable without the need to modify the existing Android apps providing the service. We analyzed its feasibility by implementing our approach and by specifying mappings for several popular Android apps, e.g., phone book, camera, and file explorer.
Keywords: Cross-Device; Integration; Android; Adapter; DSL